Mixed linear model for investigating food security during the covid-19 pandemic: Panel data for rice consumption in indonesia - Mutiara Aghnyn Aisyah; Devita Amalia Putri; Yoshua Chandra; Muhamad Syazali; Amir Machmud; Ro'fah Nur Rachmawati (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
The Covid-19 pandemic has affected human life behavior, starting from health, the economy to living habits, one of them is the rice consumption. This study aims to find out whether the Covid-19 pandemic can affect people's rice consumption, and what are the factors that can affect people's rice consumption before and during the pandemic. The independent factors studied in this study were harvested area, productivity, rice production, crime rate, and the ratio of household gas use, with rice consumption as the dependent variable. The data used is panel data for 2019 and 2020, from 34 provinces in Indonesia, which is one of the five countries with the highest rice consumption in the world. By using mixed linear models, the research results show that in general Covid-19 pandemic has not had a significant effect on rice consumption in Indonesia. Other facts also show that social factors, namely the crime rate during a pandemic, did not have a significant effect on rice consumption.However, this is different from economic factors such as productivity and harvested area which have a significant positive effect on rice consumption in Indonesia.